Evaluation of PCR Approaches for Detection of Bartonella bacilliformis in Blood Samples - Gomes, C (2016)
The objective of this study was to determine the detection limit of three PCR approaches both from blood samples as well as from filter papers. Furthermore, the specificity was also accessed. We found that the best PCR approach studied was the amplification of the 16S rRNA from blood samples with a detection limit of 5 CFU/μL, the same when using dry blood in filter paper, although the obtained bands were not so evident. Present results highlight the need to develop more sensitive techniques able to be used both in rural areas and in the detection of asymptomatic carriers. From the tested PCRs, the 16S rRNA PCR-approach is the best to be used in the direct blood detection of acute cases of Carrion’s disease.